Physical therapists familiarity and beliefs about health services utilization and health seeking behaviour - Clewley, Derek (Braz J Phys Ther, 2018)
BACKGROUND: Physical therapists’ familiarity, perceptions, and beliefs about health services utilization and health seeking behaviour have not been previously assessed. OBJECTIVES: The purposes of this study were to identify physical therapists’ characteristics related to familiarity of health services utilization and health seeking behaviour, and to assess what health seeking behaviour factors providers felt were related to health services utilization. METHODS: We administered a survey based on the Andersen behavioural model of health services utilization to physical therapists using social media campaigns and email between March and June of 2017. In addition to descriptive statistics, we performed binomial logistic regression analysis. We asked respondents to rate familiarity with health services utilization and health seeking behaviour and collected additional characteristic variables. RESULTS: Physical therapists are more familiar with health services utilization than health seeking behaviour. Those who are familiar with either construct tend to be those who assess for health services utilization, use health services utilization for a prognosis, and believe that health seeking behaviour is measurable. Physical therapists rated need and enabling factors as having more influence on health services utilization than predisposing and health belief factors. CONCLUSION: Physical therapists are generally familiar with health services utilization and health seeking behaviour; however, there appears to be a disconnect between what is familiar, what is perceived to be important, and what can be assessed for both health services utilization and health seeking behaviour.